Recombinant Human Epidermal Growth Factor/Quatsome Nanoconjugates: A Robust Topical Delivery System for Complex Wound Healing. Issue 6 (12th March 2021) - Ferrer‐Tasies, Lidia; Santana, Hector; Cabrera‐Puig, Ingrid; González‐Mira, Elisabet; Ballell‐Hosa, Lídia; Castellar‐Álvarez, Carla; Córdoba, Alba; Merlo‐Mas, Josep; Gerónimo, Haydee; Chinea, Glay; Falcón, Viviana; Moreno‐Calvo, Evelyn; et al.
Abstract: A multitude of microparticles and nanoparticles is developed to improve the delivery of different small drugs and large biomolecules, which are subject to several hindering biological barriers that limit their optimal biodistribution and therapeutic effects. Here, a soft, reliable, and scalable method based on compressed CO2 is reported for obtaining nanoconjugates of recombinant human epidermal growth factor and nanovesicles called quatsomes, where the latter consists of cholesterol and cetyltrimethylammonium bromide. These nanoconjugates exhibit appropriate values of the major critical quality attributes of colloidal nanomedicines, such as controlled and narrow nanoscopic particle size distribution (which play important roles in determining their stability), drug loading, drug release, drug protection, targeting ability, and bioactivity. Also, they exhibit a dual action by 1) inbuilt antimicrobial activity preventing infections and 2) promoting regeneration of granulation tissue and re‐epithelialization with complete closure of complex wounds. Therefore, such nanoconjugates are a potential nanomedicine for the topical treatment of complex wounds, particularly diabetic foot ulcers and venous leg ulcers. Abstract : Nanoconjugates of recombinant human epidermal growth factor and nanovesicles, composed of cholesterol and cetyltrimethylammonium bromide and prepared with a scalable method, exhibit appropriate stability, bioactivity, drug loading, releasing, protection, and targeting. These nanoconjugates show a dual action by preventing infections and promoting complete closure of complex wounds, therefore being a potential nanomedicine for the topical treatment of patients with complex wounds.